2008
DOI: 10.1590/s1517-83822008000100028
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of commercial and weathered diesel oils

Abstract: This work aimed to evaluate the capability of different microorganisms to degrade commercial diesel oil in comparison to a weathered diesel oil collected from the groundwater at a petrol station. Two microbiological methods were used for the biodegradability assessment: the technique based on the redox indicator 2,6 -dichlorophenol indophenol (DCPIP) and soil respirometric experiments using biometer flasks. In the former we tested the bacterial cultures Staphylococcus hominis, Kocuria palustris, Pseudomonas ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…This behavior was not observed in treatment 6 possibly due to a competition caused by the exogenous microorganisms. Chromatographic analyses of ASP and SB samples (Table 4) revealed that at these sites, the diesel oil was already weathered, i. e. the fuel had their characteristics altered by physical-chemical and biological mechanisms due to the large period of exposure of these compounds to the environmental conditions (Mariano et al, 2008b). Diesel oil contains 2000 to 4000 hydrocarbons, a complex mixture of normal, branched and cyclic alkanes, and aromatic compounds (Gallego et al, 2001), which cannot be totally separated by gas chromatography.…”
Section: Respirometric Biodegradation Experimentsmentioning
confidence: 99%
“…This behavior was not observed in treatment 6 possibly due to a competition caused by the exogenous microorganisms. Chromatographic analyses of ASP and SB samples (Table 4) revealed that at these sites, the diesel oil was already weathered, i. e. the fuel had their characteristics altered by physical-chemical and biological mechanisms due to the large period of exposure of these compounds to the environmental conditions (Mariano et al, 2008b). Diesel oil contains 2000 to 4000 hydrocarbons, a complex mixture of normal, branched and cyclic alkanes, and aromatic compounds (Gallego et al, 2001), which cannot be totally separated by gas chromatography.…”
Section: Respirometric Biodegradation Experimentsmentioning
confidence: 99%
“…According to Bidoia et al (2010), DCPIP is a reversible indicator, returning to its original coloration after reduction occurs. Mariano, Bonotto, De Angelis, Pirôllo, and Contiero, (2008) evaluated the rate of biodegradation of diesel and biodiesel by the colorimetric method with the redox indicator DCPIP, establishing the final time of the experiment by altering the color of the medium, from blue (oxidized) to colorless (reduced). Varjani and Upasani (2013), when assessing the hydrocarbon degradation by a bacterial consortium, recorded the lowest discoloration time of the medium in 120 hours, out of a total of 144 hours.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Similar works have reported that bacterial cultures can completely reduce DCPIP at 75, 87, 125 and 138 h for mineral oil, used oil, semi-synthetic oil and synthetic oil, respectively. [30] Mariano et al [31] performed the DCPIP assay in order to confirm that diesel oil could be degraded by bacterial consortia. Our isolates caused a colour change from blue to colourless, indicating that they have the ability to degrade crude oil.…”
Section: S Rrna Gene Sequence Analysismentioning
confidence: 99%